THE DEVELOPMENT OF GOA TABUHAN AND ITS IMPACT IN PACITAN REGENCY - Hawa Nurjannah, Siti; Adam Hilman, Yusuf; Triono, Bambang (Jurnal Partisipatoris, 2020)
This study aims at finding out the development of Goa Tabuhan and its impact asa tourist attraction. As an addition, this study also attempts to find out the efforttaken by the Tourist Office in developing the tourism sector in Pacitan regency.This study also conducted an effort comparison between the Tourist Office andWareng rural village of Punung sub-district, who manages the Goa Tabuhan touristattraction in Pacitan regency. This study used a descriptive qualitative method;there were nine informants consisted of four tourist office representatives, two of thevillage representative, two of the Goa Tabuhan local people, and one visitor of GoaTabuhan. Based on the result of the study, there is a significant impact on societyin the surrounding area of Goa Tabuhan; its visitors also experience the impact. Theimpact that affects society is in the form of economic and social and cultural effects.